2006
DOI: 10.1158/1078-0432.ccr-06-0571
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Epstein-Barr Virus, p53, Bcl-2, and Survivin in Nasopharyngeal Cancer

Abstract: Purpose: Nasopharyngeal cancer (NPC) is a malignant epithelial carcinoma which is intimately associated with EBV. The latent presence of EBV affects the function of p53, Bcl-2, and survivin. We thus investigated the relationship between EBV status, p53, Bcl-2, and survivin in biopsy specimens from patients with primary NPC. Experimental Design: Archival formalin-fixed, paraffin-embedded NPC biopsies were evaluated in 80 patients treated with curative radiation from a single institution. The presence of EBV was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 46 publications
0
61
1
3
Order By: Relevance
“…These findings suggest that the underlying mechanism of the radiosensitizing effect may involve not only prolongation of cell cycle progression but also induction of apoptosis. Notably, p53, a tumor-suppressor gene involved in numerous intracellular pathways triggered by IR exposure, is often disrupted in multiple cancers (32). The p53-independent apoptotic effect suggests that ZOL may serve as a promising tool to treat cancers, particularly those with radio or chemoresistance due to loss of p53 function (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the underlying mechanism of the radiosensitizing effect may involve not only prolongation of cell cycle progression but also induction of apoptosis. Notably, p53, a tumor-suppressor gene involved in numerous intracellular pathways triggered by IR exposure, is often disrupted in multiple cancers (32). The p53-independent apoptotic effect suggests that ZOL may serve as a promising tool to treat cancers, particularly those with radio or chemoresistance due to loss of p53 function (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-fixed and paraffin-embedded (FFPE) NPC patient biopsies were randomly selected for immunohistochemical analysis from an archival bank of materials, which have been evaluated previously. [31][32][33] qRT-PCR. Supplementary Table 3 lists all the primer sequences used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…It has already been shown that the p53 protein can bind to cellular proteins, such as the mdm2 oncogene product and heat-shock protein 70 and to several DNA tumor virus proteins, including SV40 T antigen and E1b protein from adenovirus type 5, leading to its stabilized accumulation and inactivation 38,40 . Moreover, the ability of EBV and its genes products in stabilizing or accumulating p53 protein cannot be ignored, fact confirmed by the highly significant association between EBV infection and p53 overexpression in NPC and the presence of EBV-encoded proteins that can bind and inactivate the p53 oncoprotein 45,46,47 . Thus, it is possible that one or multiple EBV genes products interact with p53 and ultimately cause its nuclear accumulation.…”
Section: Discussionmentioning
confidence: 99%